2010
DOI: 10.1007/s00066-010-2094-5
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Modulated Arc Therapy for Advanced Pancreatic Cancer

Abstract: Background: Intensity-modulated radiotherapy (IMRT) allows for improved sparing of organs at risk (OARs) in advanced pancreatic cancer. A planning study evaluated if volumetric modulated arc therapy (RapidArc™ [RA]) could be used as an alternative to IMRT in such cases. Patients and Methods: In ten patients, five-field IMRT (5f-IMRT) plans with fixed gantry positions were compared to RA plans using similar constraints for planning target volume (PTV) and OARs. PTV coverage, conformity indices (CI), and OAR dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
3
33
0
1
Order By: Relevance
“…[13] Also for locally advanced pancreas cancer, VMAT was shown to achieve similar dose levels for right kidney and significantly reduce doses for left kidney compared to 5 field IMRT. [12] In our analysis, VMAT plans revealed better overall sparing for right kidney and less amount of high dose regions for left kidney while no statistical difference was found in terms of mean dose and low dose areas for left kidney. Similar to our study design, Ali et al, analyzed 10 patients' dosimetric data and concluded that using double arc VMAT for curative or adjuvant radiotherapy for pancreas cancer patients, provides lower mean and V20-V15 doses of both kidney compared to IMRT, but other organ doses of both plans were found to be similar.…”
Section: Disclosure Statementmentioning
confidence: 48%
See 3 more Smart Citations
“…[13] Also for locally advanced pancreas cancer, VMAT was shown to achieve similar dose levels for right kidney and significantly reduce doses for left kidney compared to 5 field IMRT. [12] In our analysis, VMAT plans revealed better overall sparing for right kidney and less amount of high dose regions for left kidney while no statistical difference was found in terms of mean dose and low dose areas for left kidney. Similar to our study design, Ali et al, analyzed 10 patients' dosimetric data and concluded that using double arc VMAT for curative or adjuvant radiotherapy for pancreas cancer patients, provides lower mean and V20-V15 doses of both kidney compared to IMRT, but other organ doses of both plans were found to be similar.…”
Section: Disclosure Statementmentioning
confidence: 48%
“…In another similar dosimetric study for evaluating the use of double arc VMAT for locally advanced pancreas tumors, reduced monitor units, bilateral kidney V15 dose, mean dose of liver, stomach and small bowel dose reported. [12] Kidney dose reduction was common in all the studies. In contrast to second study, high dose regions of liver and small bowel were reduced by VMAT in our study.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, the V 35 was significantly higher with 3D-crt than with RapidArc (p = 0.007). In a comparative planning study of RapidArc and imrt conducted by Eppinga et al 19 in pcc, RapidArc was observed to modestly lower the mean dose to duodenum (p = 0.004). In our analysis, the mean dose to duodenum was similarly lower with RapidArc than with imrt (p = 0.034) or 3D-crt (p < 0.001).…”
Section: Discussionmentioning
confidence: 94%